A Cultural Perspective on Digital Transformation for Competitiveness: Integrating AI-Assisted E-Commerce, Product Diversification, Relationship Marketing, and Consumer Satisfaction - Djajanto, Ludfi; Wakhidah, Rokhimatul; Evelina, Tri Yulistyawati (Journal of Cultural Analysis and Social Change, 2026)
The aim of this study is to examine how digital transformation might enhance SMEs' competitiveness from a cultural standpoint via relationship marketing, product diversification, AI-based e-marketplaces, and customer happiness. This study's mixed, sequential, exploratory research question may have helped the data gathering lean more sharply toward quantitative or qualitative methods. 374 digitally enabled SMEs working in the culturally different areas of Malang, Yogyakarta, and Denpasar, Indonesia, made up the population. Interviewers employed questions that reflected various socio-cultural and market situations as a study tool. Data analysis was done using PLS-SEM. The empirical results show that the competitiveness of SMEs in AI-based e-commerce environments depends on product variety, relationship marketing, and customer satisfaction. AI is what drives e-commerce. This study makes significant scholarly contributions to marketing-driven digital transformation and managerial insights for those SMEs who are keen to maintain their competitive sustainability. It does this by revealing the role of customer satisfaction as a strategic bridging link between digital transformation and competitive advantage generation. As far as culture is concerned, the findings support the Resource-Based View (RBV) by showing that competitive advantage in digital transformation is deeply rooted in organizational capabilities, customer relationships, and market-oriented processes that are influenced by culture rather than being solely driven by technology.